2017
DOI: 10.1175/jas-d-16-0049.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Large Precipitating Systems and Atmospheric Factors at a Grid Scale

Abstract: In this study, TRMM-observed precipitation in the tropics is decomposed according to the horizontal area of radar precipitation features, with special emphasis on large systems (rain area > 104 km2) that contribute roughly half of tropical rainfall. Statistical associations of rain-weighted radar precipitation feature (RPF) size distributions with atmospheric variables on the 1.5° grid of ERA-Interim data are explored. In one-predictor distributions, the association with total precipitable water vapor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 137 publications
(109 reference statements)
7
17
0
Order By: Relevance
“…The convective thermodynamic and dynamic (e.g., shear) environment is known to strongly influence the development of moist convection (Stevens 2005;Sherwood 2010; Sherwood et al 2010;de Rooy et al 2013;Kim et al 2014;Virman et al 2018). These sensitivities have been examined from an observational perspective (Johnson and Lin 1997;Holloway andNeelin 2009, 2010;Tobin et al 2012;Masunaga 2012Masunaga , 2013Kumar et al 2014;Pereira de Oliveira and Oyama 2015;Bergemann and Jakob 2016;Hannah et al 2016;Schiro et al 2016;Yuan 2016;Chen et al 2017;Stevens et al 2017;Virman et al 2018), as well as via the use of high-resolution numerical models (Crook 1996;Derbyshire et al 2004;Mapes 2004;Raymond and Sessions 2007;Eitzen and Xu 2008;Wandishin et al 2008;Kuang 2010;Tulich and Mapes 2010;Cui et al 2011;Kirshbaum 2011;Hagos and Leung 2012;Böing et al 2012a,b;Hohenegger and Stevens 2013;Sessions et al 2015;Takemi 2015;Hernandez-Deckers and Sherwood 2016;Hannah 2017;Tsai and Wu 2017;Wang and Sobel 2017). Cloud microphysical processes have also bee...…”
Section: Introductionmentioning
confidence: 99%
“…The convective thermodynamic and dynamic (e.g., shear) environment is known to strongly influence the development of moist convection (Stevens 2005;Sherwood 2010; Sherwood et al 2010;de Rooy et al 2013;Kim et al 2014;Virman et al 2018). These sensitivities have been examined from an observational perspective (Johnson and Lin 1997;Holloway andNeelin 2009, 2010;Tobin et al 2012;Masunaga 2012Masunaga , 2013Kumar et al 2014;Pereira de Oliveira and Oyama 2015;Bergemann and Jakob 2016;Hannah et al 2016;Schiro et al 2016;Yuan 2016;Chen et al 2017;Stevens et al 2017;Virman et al 2018), as well as via the use of high-resolution numerical models (Crook 1996;Derbyshire et al 2004;Mapes 2004;Raymond and Sessions 2007;Eitzen and Xu 2008;Wandishin et al 2008;Kuang 2010;Tulich and Mapes 2010;Cui et al 2011;Kirshbaum 2011;Hagos and Leung 2012;Böing et al 2012a,b;Hohenegger and Stevens 2013;Sessions et al 2015;Takemi 2015;Hernandez-Deckers and Sherwood 2016;Hannah 2017;Tsai and Wu 2017;Wang and Sobel 2017). Cloud microphysical processes have also bee...…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high spatial correlations for LCL and RHM suggest that they are also useful in the prediction of intense thunderstorms. TCWV, a useful predictor for large precipitating systems (Chen et al, ), with the combination of CAPE, CIN, and SHEAR 1–3 km , does not show good performance in the estimation of intense thunderstorms with high‐flash rate. The spatial correlation related to LI 500 is relatively low, compared to other variables.…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies have shown that shear at higher levels can be important for organization (e.g., Chen et al, 2015), focusing on the lower troposphere can be justified from the results of theoretical studies such as those of Rotunno et al (1988); Thorpe et al (1982), and observational studies such as LeMone et al (1998). Likewise, Chen et al (2017) showed that deep shear was a poor predictor for MCS activity, whereas low-level shear was a better predictor. Second, we do not expect the relative rotation of the wind profiles to have a large effect on the organization that they induce.…”
Section: Overview Of Clustering Procedures Used To Generate the Representative Wind Profilesmentioning
confidence: 99%
“…The motivation for their work was to choose optimal vertical bins for the Atmospheric Dynamics Mission Aeolus satellite, and so opportunities for comparison against the work presented here are limited as they are focused on answering different questions which means their analysis cannot easily be compared with ours. Chen et al (2017) investigated the link between large-scale predictor variables and large (rain area > 10000 km 2 ) precipitation features. They used data from the Tropical Rainfall Measuring Mission (TRMM) satellite to provide information about the distribution of MCSs, and ERA-Interim to obtain information about the large-scale environment.…”
Section: Introductionmentioning
confidence: 99%